Optymalny system formacji chrześcijańskiej w Polsce - Mąkosa, Paweł (Verbum Vitae, 2012)
Due to dynamic cultural changes and related religious transformation there are many attempts to create adequate system of Christian formation in Poland. Such formation should include both the teaching of religion in schools and catechesis realized in the parish. Teaching religion in schools is an irreplaceable form of catechesis, but should be complemented by a parish catechesis. Religious education should focus on the dialogue between faith and culture and above all strengthen the cognitive dimension of catechesis. The parish catechesis should place particular emphasis on Christian initiation and preparation for the sacraments. Only the complementary model of Christian formation involving religious education in school and catechesis in the parish gives hope for the effectiveness of formation.